Delayed delivery of antibiotics by ultrasound-mediated rupture of polylactic acid pockets: In vitro and in vivo studies - Selin Isguven Billmyer; Priscilla Machado; Ryan E. Tomlinson; Lauren J. Delaney; Ji-Bin Liu; Alexander H. Harris; Eric McLaughlin; Noreen J. Hickok; Flemming Forsberg (PLoS ONE, 2025)
Surgical site infections are a devastating complication of instrumented orthopaedic surgery, particularly in the spine. Bacterial biofilms, once formed on the implant surfaces, exhibit antibiotic tolerance and immune escape, which lead to treatment challenges. Up to 9% of instrumented spine surgeries result in infection, despite the use of systemic antibiotics and local, powdered antibiotics for prophylaxis. The bacteria that survive the initial prophylaxis may be susceptible to a second, high dose of antibiotic prophylaxis prior to establishing at the site. Hence, we designed a local drug delivery system consisting of polylactic acid (PLA) film pockets that can be noninvasively triggered ( i.e. , ruptured) by the external application of ultrasound (US) following a delay of up to 6 days. We found that thin PLA films (24 ± 4.5 µm) with embedded vancomycin (VAN) powder assembled in a conical pocket shape best allowed for stability and rupturability of this US-mediated delivery system in vitro (92% US-triggered rupture of PLA-VAN pockets vs 31% of neat PLA pockets, p < 0.0001). VAN-embedded PLA films exhibited decreased strength and toughness (3.47 J/mm 3 vs 0.68 J/mm 3 , p < 0.0001) and surface VAN was rapidly released upon submersion, adding an additional layer of protection against bacterial colonization of the device. Finally, a pilot in vivo study in five rabbits demonstrated the feasibility of the design, but the stability of neat PLA and PLA-VAN pockets were varied (9/15 of all pockets were intact by Day 3). All of the 5 intact pockets (3 neat PLA and 2 PLA-VAN) that were allocated for insonation ruptured following US (100%). Overall, this design has the potential for use in targeting orthopaedic infections as well as for US-triggered bolus drug release for prophylaxis in high risk cases.